The perception of people with a physical disability towards those with a different kind of disability - Skura, Monika (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Difficulties resulting from the social perception of people with disabilities, and the personal assessment of their own disability are important for her/his relationship with other people. Therefore, it is worth asking what the perceptions are, of those who experience psychosocial effects due to their physical disability, towards people with intellectual disabilities, hearing impairments, visual impairments, mental illnesses, as well as their own physically disabled group. To analyse the perception of people with a physical disability, the study explores three areas: the acceptance or rejection of society’s stigmatization towards persons with disabilities; integrative versus separative social orientations of people with physical disability; social preferences of people with physical disability regarding other disabled people. The research sample consisted of 75 people with physical disabilities, who suffer from damage to the locomotor system. The data was collected using a questionnaire The findings highlight that the response from those who were physically disabled agreed with the opinions of general society, not only with the issue of promoting integrated solutions and offering assistance, but also having the same preferences and opinions about specific types of disability. However, their perception regarding their own group was noticeably different from that of general society.